Modelo económico para la incorporación de generación con fuentes renovables no convencionales - Masabanda Dávila, Vinicio Rubén (2015)
The study aims to find the optimal prices to encourage the generation of electricity through the use of non-conventional renewable energies such as hydro, wind, solar and biomass. For this purpose, by solving a mathematical model of nonlinear optimization, prices that allow the investor to recover the investment in a timely manner and in turn provide diversification generator Park taking into account all the parameters necessary for obtaining favorable be determined a commensurate economic value to the energy environment, thus allowing the private sector to invest in the power sector. The mathematical development is based on an economic assessment, in which values taken with which it seeks to obtain a WACC according to market environment by setting a weighted cost of capital to meet the minimum acceptable rate of return for a given project, parallel to this, the optimization model, the technical data by type of technology, the type of investment costs and operating concession terms, preferred resource usage periods included; and normative aspects that regulate the activity of generation for private enterprise